2017
DOI: 10.18378/rvads.v12i4.4980
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem matemática da cinética de secagem da casca do abacaxi

Abstract: O Brasil é o segundo maior produtor de abacaxi do mundo. A polpa é a parte do fruto que é normalmente consumida, enquanto a porção mais consistente do eixo central e a casca são consideradas resíduos do seu processamento, não sendo devidamente aproveitadas pelas indústrias. Objetivou-se com este trabalho desidratar a casca do abacaxi, na forma de placas com comprimento de 15 cm e largura de 8 cm, em estufa com circulação forçada de ar nas temperaturas de 75 e 85 °C, e ajustando-os a modelos matemáticos. Como c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…The residual peel samples had an average initial moisture con- The Page model also provided the best fits for Leite et al (2017) when studying the drying kinetics of pineapple peel in an oven with forced air circulation at temperatures of 75 and 85 C, and for Gonçalves et al (2016) when studying the drying kinetics of green banana peel and pulp in an oven at temperatures of 55, 65, and 75 C.…”
Section: Drying Kineticsmentioning
confidence: 96%
See 1 more Smart Citation
“…The residual peel samples had an average initial moisture con- The Page model also provided the best fits for Leite et al (2017) when studying the drying kinetics of pineapple peel in an oven with forced air circulation at temperatures of 75 and 85 C, and for Gonçalves et al (2016) when studying the drying kinetics of green banana peel and pulp in an oven at temperatures of 55, 65, and 75 C.…”
Section: Drying Kineticsmentioning
confidence: 96%
“…The experimental drying kinetics curve and the curves predicted by the mathematical models are specific to each type of material. Much data have been published in the literature on the determination and mathematical modeling of the thin layer drying of agricultural products and agro-industrial waste, such as pitaya peel (Santos, Figueirêdo, Queiroz, & Santos, 2017), pineapple peel (Leite et al, 2017), andiroba seeds (Mendonça, Sampaio, Almeida, Ferreira, & Novais, 2015), and jackfruit seeds (Leite, Queiroz, Figueirêdo, & Lima, 2019), but no studies were found concerning the drying of the pulp, peel, or seeds of trapi a fruit. Thus, the objective of this study was to determine the drying kinetics of the residual peel and seeds of trapi a fruit, fit the experimental data to 10 mathematical models, and determine the thermodynamic properties of the products for the process.…”
mentioning
confidence: 99%
“…Isso ocorre devido a maior taxa de remoção de água no interior do produto, que é influenciada pela maior transferência de energia na forma de calor [14].…”
Section: Resultsunclassified
“…Segundo Madamba et al (1996), o coeficiente "k" está relacionado com a difusividade efetiva no processo de secagem. Conforme relatado na literatura, outros autores também constataram aumento da constante "k" conforme incremento da temperatura do ar de secagem (Martinazzo et al, 2010;Goneli et al, 2014;Silva et al, 2015;Leite et al, 2017;Mghazli et al, 2017;Santos et al, 2019).…”
Section: Cinética De Secagemunclassified